Actividad específica de la Glucosa-6-fosfato deshidrogenasa (EC 1.1.1.49) en tejido adiposo y hepático durante la exposición a la altura - Gonzales R., Alberto (1999)
The Glucose-6-phosfate dehydrogenase (G6PD) specific activity was determined in adipose and hepatic tissues 0167 Holtzman, male, adults rats, born and bred at sea level. Of them, 48 were transported by automobile in three hours up to 4 540 m. above sea, and sacrificed in turn at 0,1,2,3,5,15 and 30 days after arrival. The other 19 were grouped in two classes: a control class of rats which never traveled, and another class of rats thal traveled around fer three hours, after which they were sacrificed.As a result, it was shown that the trip without ascenl did not cause any significant variation in adipose and hepatic tissue G6PD specific activity.In animals taken to the high altitude, it was observed a lower specific activity of adipose tissue G6PD than in those remaining at sea level. During the first two days the activity fell sharply, thereafter recovering slowly without actually returning to initial value al arrival.As to the hepatic tissue, G6PD specific activity in animals, taken to the high altitude it arose from the arrival, stayed above those at sea level without showing significant al changes during 15 days at high altilude, with a slight increase al day 30 after arrival.